2010
DOI: 10.1590/s0100-736x2010000300006
|View full text |Cite
|
Sign up to set email alerts
|

Doenças neurológicas de ovinos na região central do Rio Grande do Sul

Abstract: .br A retrospective study of neurological diseases of sheep in southern Brazil was conducted over an 18-year period (1990-2007). A data base search was carried out in the files of the Laboratory of Veterinary Pathology (LPV) of the Universidade Federal de Santa Maria (UFSM), central Rio Grande do Sul state, Brazil. A total of 586 sheep were examined. These cases corresponded to necropsies performed in the LPV-UFSM or to mailed in samples from practitioners. Out of these, 69 experimental cases were excluded fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
(25 reference statements)
3
7
0
3
Order By: Relevance
“…The most significant lesions occurred in the brainstem, and were found unilaterally and characterized mainly by microabscesses, areas of malacia, and perivascular cuffs, similar to what has been observed in cattle (Sanches et al 2000, Oevermann et al , Margineda et al 2012, goats (Rissi et al 2006, Headley et al 2013, and sheep (Rissi et al 2010, Headley et al 2013.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The most significant lesions occurred in the brainstem, and were found unilaterally and characterized mainly by microabscesses, areas of malacia, and perivascular cuffs, similar to what has been observed in cattle (Sanches et al 2000, Oevermann et al , Margineda et al 2012, goats (Rissi et al 2006, Headley et al 2013, and sheep (Rissi et al 2010, Headley et al 2013.…”
Section: Discussionsupporting
confidence: 73%
“…In Brazil, the encephalitic form of listeriosis in ruminants has already been described in cattle (Sanches et al 2000, Konradt et al 2017, goats (Rissi et al 2006, Guedes et al 2007, Konradt et al 2017, and sheep (Mendes et al 2005, Ribeiro et al 2006, Guedes et al 2007, Rissi et al 2010, Konradt et al 2017, but this form of the disease has not been reported in buffaloes to date. Therefore, this study aimed to describe an outbreak of listeric meningoencephalitis in buffaloes.…”
Section: Introductionmentioning
confidence: 99%
“…Nos estudos de casuística das doenças neurológicas realizados no Brasil, a raiva sempre é apontada como a principal enfermidade do SNC nos bovinos (Sanches et al 2000, Galiza et al 2010, Ribas et al 2013 e uma das principais nos equídeos (Lima et al 2005, Pimentel et al 2009). O mesmo não é verdadeiro para os ovinos e caprinos, nos quais a doença é observada em número pequeno de casos (Lima et al 2005, Guedes et al 2007, Rissi et al 2010. Também no PR, estudo prospectivo sobre o diagnóstico diferencial de doenças neurológicas em 136 bovinos, realizado entre 2009 e 2012, revelou que 38% dos animais (n=51) apresentavam encefalite, causada principalmente pelo vírus da raiva (n=16) e por BoHV-5 (n=20) (Queiroz et al 2013).…”
Section: Resultsunclassified
“…In sheep, the main predisposing factor previously described is caudectomy, which favors ascending bacterial infections and culminate with spinal cord meningomyelitis and abscesses (Rissi et al 2010). According to Kessell et al (2011), young animals less than one year-old are more frequently affected by cerebral abscesses than adult ruminants, differing from the present study, which has found that cerebral abscesses affected mainly adult ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…The main inflammatory neurological diseases caused by bacteria in ruminants are: listeriosis, suppurative leptomeningitis and meningoencephalitis, cerebral and spinal cord abscesses, basilar empyema and neurotuberculosis (Loretti et al 2003, Rissi et al 2010, Câmara et al 2014, Konradt et al 2016. CNS may be affected by infectious agents through four paths: from hematogenous or lymphatic dissemination deriving from distant sites (Morin 2004, Stöber 2005; direct penetrating lesions; through an adjacent suppurative lesion; or centripetal ascending infection through peripheral nerves 2006, Radostits et al 2007.…”
Section: Introductionmentioning
confidence: 99%